Elucidation of the mechanism Underlying the promotion of ferroptosis and enhanced antitumor immunity by citrus polymethoxyflavones in CRC cells - Duan, Yingying; Wu, Yu; Tian, Jiaqi; Yin, Yuqin; Yuan, Zhongwen; Zhu, Wenting; Zhou, Suyue; Li, Chen; Feng, Senling (Frontiers in Pharmacology, 2025)
BackgroundColon cancer is a prevalent condition with a high mortality rate on a global scale. Research has indicated that Citrus polymethoxyflavones (PMFs), a class of flavonoids found in Citrus, possess the potential to demonstrate anti-tumor efficacy. Ferroptosis a form of cell death that is dependent on iron accumulation and lipid peroxidation. Immunotherapy is one of the most commonly used anti-tumor modalities in a clinical setting. Consequently, studies on the pharmacodynamic mechanism of Citrus to determine whether it can modulate tumor immunity through ferroptosis provide new ideas for the clinical treatment of colon cancer.PurposeThe objective of this study is to ascertain whether Citrus inhibits PD-L1 through ferroptosis and promotes tumor immunity among patients with colon cancer.MethodsThe inhibitory effect of PMFs on colon cancer was proved by in vitro experiment and in vivo model. In addition, the occurrence of ferroptosis was detected by measuring key ferroptosis indicators. Bioinformatics analysis was then performed to identify the crossover genes for Citrus polymethoxylflavonoids, colon cancer, and ferroptosis. Finally, key genes were identified by immunocorrelation analysis including WB, Q-PCR and flow cytometry. These experiments were designed to reveal the potential mechanisms of PMFs on ferroptosis and anti-tumor immunity.ResultsIn vitro cell proliferation experiment and the growth of transplanted tumor mice showed that PMFs had inhibitory effect on colon cancer. In addition, the change of ferroptosis index showed that PMFs promoted the occurrence of ferroptosis, followed by Q-PCR and WB detection of NOX4 and TIMP1, the key genes screened by bioinformatics, found that PMFs inhibited PD-L1 by down-regulating TIMP1, thus affecting colon cancer. Flow cytometry showed that CD4+ T expression increased and CD8+ T cell expression decreased after treatment, suggesting that anti-tumor immunity was activated.ConclusionIt is conceivable that the tumor immune microenvironment may be subject to regulation during the inhibition of colon cancer through ferroptosis in PMFs. The ferroptosis-related gene TIMP1 has been observed to regulate PD-L1, thereby promoting anti-tumor immunity in colon cancer. However, further investigation is required to ascertain the underlyingprecise mechanisms.